Occurrence and experimental introduction of Capricornia boisduvaliana (Duponchel, 1836) (Lepidoptera: Tortricidae) in Finland - Välimäki, Panu; Itämies, Juhani (Entomologica Fennica, 2002)
The rapid decline of Capricornia boisduvaliana in Finland during the past two decades is summarised. The only known occupied meadow is located in northern Finland, in the vicinity of Rovaniemi. The distribution of the species in two provinces (Oba and Obb) was surveyed in 1998 by searching through 95 sites. No other occupied sites were found. The biology of the species was also studied. Larvae overwinter as half-grown and feed on Trifolium pratense L. close to the ground, where they spin silken webs around the base of the food plant and among protective litter. In Finland, the species is currently critically threatened, and restoration of habitat and experimental introductions were, therefore, started in the summer 1999 in Rovaniemen mlk. close to the known occupied site. The eggs produced by 15 females were divided into three groups and transported onto three restored meadows. Habitat restoration at three other sites was also started in the same summer. The next summer, reinforcement + introductions were carried out. After the first two years, both larvae and adults were observed at two introduction sites. Restoration of habitats continued in 2001.